The formation of friction blisters on the foot: the development of a laboratory‐based blister creation model. Issue 1 (14th August 2012) - Hashmi, Farina; Richards, Barry S; Forghany, Saeed; Hatton, Anna L; Nester, Christopher J
<x xml:space="preserve">Abstract</x> Background/Purpose Friction blisters on the foot are a debilitating pathology that have an impact on activities of daily living and can severely impair function. The purpose of this study was to test the hypotheses that digital infrared thermographic imaging will reveal: 1) a correlation between load application to the skin and the creation of blisters, and 2) a correlation between thermographic readings and contact thermometric temperatures. Methods Apparatus was developed to cause the formation of heel blisters through controlled load application (70 kPa). One foot of each of the 30 healthy volunteers (21 men and 9 women), with an age range of 31 ± 8 years, was subjected to load until a blister formed, after which load application ceased and temperature measurements were taken at set times during the following 5.5 h. Temperature measurements were also taken using a contact thermometer. Results The majority of the participants (77%) blistered within 18 min of load application. All the blisters created showed significant increases in local temperature compared to baseline during blister creation (P < 0.001) and 30 min post‐blister creation (P < 0.001). There was a strong correlation between contact thermometry and thermographic temperature data (r > 8). Conclusion These results suggest that thermographic images may prove useful for the remote assessment of traumatically damaged foot skin.